Benvenuto Terracini en la Argentina: Del ‘efecto Auerbach’ al ‘efecto Alonso’ - Bentivegna, Diego Luis (2022)
In this essay, we go through some aspects of the Argentine production made by Italian linguist, philologist and critic Benvenuto Terracini. As a consequence of the so-called ‘racial laws’ of anti-Semitic content enacted in Italy in 1938, Terracini, one of the main figures in the studies on languages in twentieth century Italy, moved to Argentina and worked during the 1940s at the University of Tucumán as professor of Linguistics. Our main focus is the conceptual and methodological ‘turn’ that occurred in the Tucumán years of Terracini’s production, a turn that is materialised with the emphasis on the question of subjectivity and style. We relate this conceptual turn of Terracini with some lines of work, which were at that time powerful in philological studies in Argentina, especially the impulse of stylistic studies undertaken by the Spaniard Amado Alonso during his time as director of the Institute of Philology of the University of Buenos Aires, whose last stage coincides with Terracini’s exile from Tucumán. Also taken into consideration are the glotopolitical implications of the Argentine production of the Italian linguist starting, fundamentally, from the concept of ‘linguistic freedom’.